The clinical spectrum of viridans group streptococcus bacteraemia in paediatric patients at Chris Hani Baragwanath Academic Hospital - Shongwe, Nkosinathi Sifiso (University of the Witwatersrand, Johannesburg, 2023)
Background: Viridans group streptococci (VGS) are often considered organisms of low virulence; however, infection can result in clinically significant sepsis and life-threatening complications in paediatric patients. Objectives: To describe the spectrum of clinical presentation of VGS bacteraemia in paediatric patients, to analyse risk factors, and to describe the antibiotics resistance patterns of VGS. Methods: Cultures of VGS in paediatric patients admitted to Chris Hani Baragwanath Academic Hospital in 2019 were retrieved from NHLS data base. Data was extracted from archived clinical records and analysed. Sepsis scores were calculated at the time of bacteraemia. Results: 133 cultures were identified; 64 (48.1%) polymicrobial cultures (64) and no records 4 (0.03%) were excluded; 65 (48.9%) were analysed. The median age was 1.5 months (range 0.03 to 168, Interquartile range (IQR) 0.2 to 13.25), 27/65 (42%) were neonates. The median duration of hospitalisation was seven days (IQR 3 to 21). The commonest diagnoses were neonatal sepsis 30.8% (n=20) and pneumonia 28% (n=18). The systemic inflammatory response syndrome (SIRS) score was ≥2 in 57% (16/28) patients; paediatric sequential organ failure assessment (pSOFA) score was >2 in 10/24 (42%). Fifty-seven (88%) patients were discharged; three (5%) required ICU admission and 8/65 (12.3%) died. Malnutrition was present in 50% of patients who died. Cephalosporins and penicillin had susceptibility of 89% and 55% respectively. Conclusion: VGS bacteraemia was common in neonates, and pneumonia was a common presentation in this cohort outside the neonatal period. VGS bacteraemia was associated with morbidity and deaths in this cohort. Contribution: VGS should be considered a significant organism when cultured and routine antibiotic susceptibility testing should be performed. Prospective studies are recommended.
A research report submitted in partial fulfilment of Master of Medicine in paediatrics degree in the department of Paediatrics and Child Health, to the Faculty of Health Science, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Viridans group streptococci (VGS); Paediatric patients; Chris Hani Baragwanath Academic Hospital; Systemic Inflammatory Response Syndrome (SIRS); VGS bacteraemia; Paediatrics; Children health; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education